The lightness of hands - Garvin, Jeff (Balzer + Bray, an imprint of HarperCollins Publishers, 2020)
Sixteen-year-old Ellie Dante tries to stage her down-and-out magician father's comeback in order to pay for medication for his heart condition and her bipolar II disorder.